(untitled) (Journal of history, 2021)
The territory of Zhetysu is distinguished by a unique concentration of monuments of the Saka time of the I millennium BC. The funeral rite is one of the key elements of the culture of any ethnic group. Funeral and memorial complexes of the Saka time on the territory of Zhetysu are relatively well studied today. Despite significant achievements in recent decades, the cultural and chronological aspects of the Saka cultures are little developed, where the design features of funeral monuments play an important role. The purpose of our research is to determine the local features and trace the genesis in the burial practice of the Saka on the territory of Zhetysu. From a methodological point of view, the article contains, first of all, traditional archaeological research methods: mapping, planographic and stratigraphic observations, classification of clothing com- plexes, the method of analogies, formal typological analysis, elements and methods of statistics, the retrospective method. In the classical Saka time (V–IV centuries BC), the Zhetysu region was localized in terms of a funeral and memorial rite. There are changes in the funeral rite and inventory in general. Studying the design features of the mounds, we came to the conclusion about the local originality of the burial traditions of local tribes. The previously unpublished design features of the so-called “colored” mounds were noted. Key words: South-Eastern Zhetysu, Shelek-Talgar interfluve, early nomads, kurgan, construction, genesis.